The Impact of Service Quality and Location on Consumer Purchase Decisions: A Case Study of Pecel Lele Wahyu Kalangsari, Rengasdengklok - Aditiya; Sihabudin; Robby Fauji (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — The purpose of this study is to examine the impact of service quality and location on consumer purchasing decisions at Pecel Lele Wahyu Kalangsari, a small and medium-sized enterprise (SME) in Rengasdengklok. Given the increasing competition in the culinary industry, understanding the factors that influence customer behavior is essential for enhancing business performance and ensuring customer retention. Research method—A quantitative research approach was employed using a descriptive-verification design. Data were collected through a structured questionnaire distributed to 72 customers selected using simple random sampling. The questionnaire measured perceptions of service quality (using the SERVQUAL model), location accessibility, and consumer purchase decisions. Multiple regression analysis was conducted to analyze the relationships between service quality, location, and consumer purchasing decisions. Result— The study found that both service quality and location have a significant positive influence on consumer purchasing decisions. The service quality had the highest impact, with a beta coefficient of 0.482, followed by location, with a beta coefficient of 0.358. The combined effect of both variables explained approximately 52.4% of the variance in consumer purchasing decisions. This suggests that improvements in both areas could lead to increased customer satisfaction and repeat business. Conclusion— This study confirms that both service quality and location are critical factors in influencing consumer purchasing decisions at Pecel Lele Wahyu Kalangsari. Business owners should focus on improving service quality through employee training and customer interaction, while also considering the strategic location of their establishments to enhance accessibility and visibility. These findings provide valuable insights for SMEs in the culinary sector to optimize their strategies for improving customer engagement and boosting sales. Future research could explore the role of additional factors, such as pricing and marketing strategies, in shaping consumer behavior.